Śladem romantycznej kreacji bohatera w chorwackiej poezji końca XX wieku. Od wampira do konsumenta - Pieniążek-Marković, Krystyna (Wydawnictwo Rys (nr 1), 2011)
One of the distinctive traits of Romantic literature was its frenetic feverishness and frightening otherness, the embodiment of which was, among many other beings, the vampire. This character in neo-Romantic contexts was sometimes invoked by the representatives of Croatian poetry of the late twentieth century. However, in its different currents it performed a different task. War and martyrdom poetry collected in the anthology U ovom strašnom času used the specter for the creation of a portrait of the enemy, while using the familiar clichés of Renaissance variant of Croatian romanticism. Branko Maleš’ vampiric themes merge into an indivisible whole with references to contemporary consumerism and co-create an ironic self-portrait of a postmodern neo-Romanticist. Maleš reaches for the themes of romantic strangeness and deconstructs them in a ludic manner.
Tracing the Romantic creation of character in Croatian poetry of the end of the 20th century. From vampire to consumer
Keywords: Vampire; Consumption; Croatian poetry; War lyric poetry; Maleš; Neo-romanticism